1991
DOI: 10.1093/oxfordjournals.humrep.a137372
|View full text |Cite
|
Sign up to set email alerts
|

Co-treatment with growth hormone of sub-optimal responders in IVF-ET

Abstract: Several growth factors augment the ovarian response to gonadotrophins and growth hormone is known to regulate the production of insulin-like growth factor-1. With this in mind, 20 women who had previously responded sub-optimally to standard ovarian stimulation regimens for in-vitro fertilization and embryo transfer (IVF-ET) were recruited into a randomized trial to study the effect of co-treatment with growth hormone (Norditropin, Novo Nordisk Gentofte A/S). Intramuscular injections of growth hormone (24 IU) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
1
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 0 publications
0
41
1
1
Order By: Relevance
“…In fact, several studies have demonstrated that GH treatment increases ovary sensitivity to gonadotropin stimulation in infertile women with hyposensitive ovaries (12)(13)(14)(15)(16)(17)(18)(19). The effect of GH administration on gonadal function in men has been poorly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several studies have demonstrated that GH treatment increases ovary sensitivity to gonadotropin stimulation in infertile women with hyposensitive ovaries (12)(13)(14)(15)(16)(17)(18)(19). The effect of GH administration on gonadal function in men has been poorly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Following the hypothesis that G H or IGF-I can facilitate granulosa cell responsiveness to gonadotrophins, a series of studies demonstrated that co-treatment with G H augmented the ovarian response to stimulation by gonadotrophins (Homburg et al. 1988;1990a;Owen et al, 1991a;Blumenfeld & Lunenfeld, 1989;Volpe et al, 1989;Menashe rt al., 1990). On the basis of the encouraging results achieved in these studies and the demonstration in pubertal boys of a Spermatogenesis requires the stimulatory effects of FSH, LH and adequate testosterone (T) concentrations (Matsumoto & Bremner, 1989).…”
mentioning
confidence: 99%
“…91]. Several studies have demonstrated the utility of exogenous GH to enhance ovarian responsiveness in women with previously poor responses to hMG therapy [21, [92][93][94]. GH is the primary regulator of serum IGF-I levels [3,95].…”
Section: Igf Responses During Ovulation Induction Igf I During Gh Trementioning
confidence: 99%
“…Clinical trials have demonstrated that administration of recombinant human GH in superovulation protocols for women who have previously shown poor clinical responses to hMG therapy results in significantly increased numbers of preovulatory follicles and peak E2 levels, while simultaneously reducing hMG dose requirements [21, [92][93][94]. In a randomized double-blind, placebo-controlled study with recombinant human GH and hMG given to 16 patients with amenorrhea and anovulatory infertility [21], the required dose of hMG decreases 36%, the number of days of treatment decreases 25%, and the daily effective dose decreases 19%.…”
Section: Igf Responses During Ovulation Induction Igf I During Gh Trementioning
confidence: 99%
See 1 more Smart Citation